2014
DOI: 10.3844/ajisp.2014.73.87
|View full text |Cite
|
Sign up to set email alerts
|

Moringa Tea Blocks Acute Lung Inflammation Induced by Swine Confinement Dust Through a Mechanism Involving TNF-α Expression, C-Jun N-Terminal Kinase Activation and Neutrophil Regulation

Abstract: Plant based products represent a promising alternative to conventional treatments for inflammation. Moringa oleifera Lam is a tree rich in proteins, vitamins, minerals and a variety of phytochemcals with health benefits. Among the reported health benefits are antioxidant and anti-inflammatory properties. The purpose of this study was to investigate whether tea brewed from dried Moringa leaves would abrogate inflammation in a mouse model of acute lung inflammation induced by LPS or extracts prepared from dust c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
(60 reference statements)
2
6
0
2
Order By: Relevance
“…M. oleifera leaf tea studies demonstrated alterations in blood circulating neutrophils and conclude that Moringa tea has adaptogenic capabilities in cases of stress (Drue et al 2018 ) (Table 5 ). Previous studies using dried Moringa leaves tea in mouse model with acute lung inflammation, showed that mice that had decreased lung inflammation marked by alterations in cytokine production, leukocyte migration, and neutrophil apoptosis (McKnight et al 2014 ). An ethanolic extract of Moringa leaves has anti-anxiety effect in swiss albino mice, the ethanolic extract of M. oleifera leaves may have produced its anxiolytic effects via multiple mechanisms (Bhat 2014 ).…”
Section: The Resources Obtained From M Oleifera Tmentioning
confidence: 99%
“…M. oleifera leaf tea studies demonstrated alterations in blood circulating neutrophils and conclude that Moringa tea has adaptogenic capabilities in cases of stress (Drue et al 2018 ) (Table 5 ). Previous studies using dried Moringa leaves tea in mouse model with acute lung inflammation, showed that mice that had decreased lung inflammation marked by alterations in cytokine production, leukocyte migration, and neutrophil apoptosis (McKnight et al 2014 ). An ethanolic extract of Moringa leaves has anti-anxiety effect in swiss albino mice, the ethanolic extract of M. oleifera leaves may have produced its anxiolytic effects via multiple mechanisms (Bhat 2014 ).…”
Section: The Resources Obtained From M Oleifera Tmentioning
confidence: 99%
“…The medicinal plant sorrel ( Hibiscus sabdariffa , rosell), rich in phenolic acids, flavonoids and lignans, possesses antioxidant, anti-inflammatory, antimicrobial and anti-tumerogenic properties [119-121]. In a recent study by our group, Moringa olifera Lam leaf extract – a medicinal plant rich in vitamins, including vitamin D [122] -- reduced acute lung inflammation mediated by intranasal exposure to ODE in mice that consumed water supplemented with moringa compared to control mice that drank water [123*]. The study showed mice that drank moringa tea had fewer cells present in bronchoalveolar lavage, despite having higher ODE-driven TNF-α levels, a finding that is consistent with observations of Mahajan et al [124] in which a moringa seed extract decreased bronchoalveolar lavage fluid (BALF) cell counts, but did not affect TNF-α levels in guinea pigs exposed to aerosolized ovalbumin [124].…”
Section: Potential Therapeutic Benefits Of Dietary Phytonutrients Andmentioning
confidence: 99%
“…Vitamin D was reported to inhibit organic dust-induced proinflammatory cytokines in vitro (human airway epithelial cells and monocytes) and ex vivo (mouse lung slices) [14]. Mice exposed to hog barn dust but allowed to consume Moringa tea had fewer white blood cells present in bronchoalveolar lavage than mice only drinking water [15]. Hibiscus sabdariffa (sorrel) of the Malvaceae family is a plant native to the West Indies, Jamaica, and China and has been grown in the United States.…”
Section: Introductionmentioning
confidence: 99%